Sime Darby Property - Mohd Asmir, Muhammad Danish Rifqi; Mohd Zakri, Putra Shahrul Harif; Ruslan, Aleeya Maisara; Mohd Nizam, Norhana Najwa (2024)
In this comprehensive report, we meticulously delineate all the activities undertaken during our in-depth case study at Sime Darby Property, Ara Damansara. Our focus revolves around the nuanced intricacies of building maintenance management as orchestrated by the adept team at the building maintenance department. The report encapsulates a wealth of information gleaned directly from the building and the maintenance department, meticulously curated to fulfil the task requirements. Comprehensively meeting the stipulated criteria, we delve into the specifics of property details, organizational structures, and the intricacies of maintenance management within the building. Addressing the multifaceted requirements, our report systematically unfolds the maintenance policy and planning, the technological underpinnings of the building design, and the dynamic interplay of maintenance strategies. Furthermore, we navigate through a thorough building condition assessment, shedding light on the maintenance strategies employed. Legal aspects are scrutinized, providing a holistic view of the case study. The financial intricacies, including the maintenance budget, are presented with analytical precision. Throughout, we dissect problems encountered and proffer insightful recommendations based on rigorous analysis. Our report stands as a comprehensive compendium, encapsulating insights furnished by the adept maintenance department at our case study location. It affords readers a panoramic view of the maintenance management landscape from our perspective as students. The crux of our argument emphasizes the pivotal role of maintenance in preserving property value over time, minimizing inconveniences, and ensuring the safety of building occupants. We ardently hope that the detailed contents of this report not only meet but exceed the expectations of our readers, imparting a wealth of knowledge in the intricate realm of building maintenance management.